Engineering of composite materials made of epoxy resins modified with recycled fine aggregate - Krzywiński Kamil (De Gruyter, 2021)
The paper presents studies performed on polymer-cementitious composite made of epoxy resin coating modified with aggregate and cementitious substrate. Epoxy resin is a perfect material that can be used to protect cementitious materials. According to its manufacturer, it can be mixed with fine aggregate. Coarse aggregate made of building demolition wastes is mostly utilized in concrete mixtures or road structures. Fine aggregate is not widely used. Therefore, the novelty of this research was the utilization of recycled fine aggregate (RFA) in epoxy resin coatings. Natural fine aggregate (NFA) was also used as an extender in the coating. The natural aggregate in the coating was partially replaced with recycled aggregate in amounts of 0, 20, 40, 60, 80, and 100% of its weight. Sixteen specimens of polymer-cementitious composites were prepared for the flexural tensile strength test, and thirty-two specimens for the compressive strength test. The macroscale tests were performed after 35 days of curing (28 days – cementitious substrate, and 7 days – epoxy resin). The results show that the epoxy resin coating does not affect the flexural tensile and compressive strength of the analyzed composites. Moreover, the type of aggregate used in the coating does not have a significant impact on the measured properties of polymer-cementitious composites. Economic analysis was performed in order to estimate the cost of the natural and RFAs used in epoxy resin coatings. The calculations show that a higher amount of RFA should be used to increase savings.